Donor Harvesting by Direct Visualization of the Hair Follicle - Pathomvanich, Damkerng (The Thai Journal of Surgery, 2004)
Background: There are several methods for harvesting donor hair such as punch excision, single-bladed knife excision, and multibladed knife excision. All of these procedures are blind and thus resulted in transection of hair follicles and fewer follicles being available for transplantation that detrimentally affect the final cosmetic results. Objective: To explore a new method of donor hair harvesting called "donor dissecting". This new procedure is an open technique as hair follicles are directly visualized during the harvesting process. Materials and Methods: The technique of donor dissecting utilizes a #15 scalpel blade for single strip harvesting from the occiput while maintaining meticulous hemostasis. This enables individual hair follicle to be visualized and protected from transection during the harvesting process. Once the single strip is harvested, it is then further divided into individual follicular unit or mini- and micro-grafts using direct visualization of individual follicles to again prevent transection. Result: The technique of donor dissecting was utilized in 50 consecutive hair transplant patients. Utilizing this new technique, only 1.9 % of hair follicles in the donor strip were transected during the harvesting process. At the dissection of donor strip 1.2% follicles were transected in the grafts cutting process. Combining the donor dissecting technique with dissection of the individual grafts, the transection of hair follicles was 1.59%. Conclusion: The technique of donor dissection minimizes the transection of hair follicles in the donor hair harvesting phase of hair transplantation. This technique is superior to the blind methods of donor harvesting which have been plagued by the problem of excessive hair follicle transection.